PENGARUH KOMPETENSI DAN INDEPENDENSI AUDITOR DALAM TAHAPAN PENYELESAIAN AUDIT ATAS LAPORAN KEUANGAN “Studi Kasus Pada Kantor Akuntan Publik Kota Malang” - Ni Wayan Indah Suwarningsih; Zulfikar Ismail (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2012)
The research aimed at testing whether the competence and independence of auditor influences the audit solution stage to the financial report. The research data were obtained through questionnaires. The research obtained responses of 33 from senior auditors, managers and partners from 6 Public Accountant Offices in the Malang City. The independent variables in the research were competence and independence, while the dependent variable was the audit completion. The research was analyzed by using multiple regression analysis as analysis model. Based on the research results, it can be concluded that partially and simultaneously the competence and independence influence to the audit completion. The results showed that to improve the audit completion influenced by two variables, competence and independence. Competent auditors have many experiences and sufficient trainings that influence the audit completion, auditors are said as independent if they are not influenced by pressures and the long term relation with the client. Keywords: : auditor competence, auditor independence, and audit completion